Relational identities and other-than-human agency in archaeology - Harrison-Buck, Eleanor, editor; Hendon, Julia A., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2018)
Explores benefits and consequences of archaeological theorizing on and interpretation of social agency of non-humans as relational beings capable of producing change in the world. Cross-examines traditional understanding of agency and personhood, presenting globally diverse case studies that cover a range of cultural, geographical, and historical contexts.--Provided by publisher.
An introduction to relational personhood and other-than-human agency in archaeology / Eleanor Harrison-Buck and Julia A. Hendon -- Personhood and agency in Eskimo interactions with the other-than-human / Erica Hill -- Dead kettles and indigenous afterworlds in early colonial encounters in the Maritimes / Meghan C. L. Howey -- Water and shells in bodies and pots: Mississippian rhizome, Cahokian poiesis / Timothy R. Pauketat and Susan M. Alt -- The inalienable-commodity continuum in the circulation of birds in the North American Plains / María Nieves Zedeño, Wendi Field Murray, and Kaitlyn Chandler -- Objects with voices among the ancient Maya / Matthew Looper -- Can tools have souls?: Maya views on the relations between human and other-than-human persons / Julia A. Hendon -- Torres Strait canoes as social and predatory object-beings / Ian J. McNiven -- Efficacious objects and techniques of the subject: "ornaments" and their depositional contexts in Banda, Ghana / Ann B. Stahl -- Finding objects, making persons: fossils in British Early Bronze Age burials / Joanna Brück and Andrew Meirion Jones -- Relational matters of being: personhood and agency in archaeology / Eleanor Harrison-Buck.
Keywords: Social archaeology -- Case studies; Agent (Philosophy) -- Case studies; Material culture -- Philosophy; Archaeology -- Philosophy